Prevalence and impact of adiposity and sarcopenia during rheumatoid arthritis: rapid and non-invasive evaluation in Sub-Saharan African women - Touré, Maïmouna; Diagne, Mouhamed T.; Badji, Amadou; Thiam, Souleymane; Diouf, Coumba; Niasse, Moustapha; Sene, Mbaye; Sow, Abdou Khadre; Seck, Aissatou; Houndjo, Salimata D.; Diaw, Mor; Mbengue, Arame; et al. (International Journal of Research in Medical Sciences, 2019)
Background: Body composition plays a fundamental role in the occurrence of complications in rheumatoid arthritis. Authors conducted this study, which aimed to determine body composition and its effects on physiological status in African sub-Saharan polyarthritis women. Methods: The anthropometric parameters were measured after an interview and a complete physical examination. The body composition was evaluated using a Tanita® brand bioimpedance meter. Finally, all the patients had a dosage of certain biochemical parameters. Results: An excess of percent fat mass was noted in more than half of women (59.52%) without loss of muscle mass. At the same time, 30% of women had a significant decrease in the percentage of body water. The BMI did not appear to be an adequate proxy for these changes. Visceral fat level was elevated just in 16% of women, however it would be a determinant of physiological aging of subjects. Dual therapy methotrexate and corticosteroid would have varying effects depending on the duration and the dose of treatment. The basic metabolism in polyarthritic subjects would be dependent on two parameters namely muscle mass and inflammatory state. Conclusions: Evaluating changes in body composition quickly, non-invasively and inexpensively is possible. It could be useful in the follow-up of rheumatoid arthritis. Managing these changes can reduce cardiovascular morbidity and mortality in rheumatoid arthritis.